Types of Speech Acts Spoken by Livi Redden on Video “What Nobody Tells You About Your Twenties” (2023) on Youtube - x, Reviana; Rofik, Abdur (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2025)
This study is aimed to find out (1) types of speech acts and (2) the function of types of speech acts spoken by Livi Redden on video